Destruction of the Kražiai Rural District Jewish Community in 1941: Some Facts, Problems, Answers, Pending Questions - Buchaveckas, Stanislovas (Genocidas ir rezistencija, 2009)
The article is aimed at revealing events in the summer of 1941 in the Kražiai Rural District of the Raseiniai County, related to the holocaust, the specificities of those crimes in that local territory of Lithuania‘s province, showing, even if a minor basis of the sources is available, the role of Nazis, method and “technologies”, applied for attracting Lithuanians into the measures and actions for denaturalization of Jews as Lithuanian citizens and their isolation, as well as recreating, where possible, the last criminal act – a massacre which had the specific features in each rural district.The Jewish ghetto in Kražiai where later also Jews from Karklėnai village with a church were placed was established in the former court barn near the township. At first, it was guarded by German soldiers, later by Lithuanians. For killing Jews (about 350 victims) the Nazis used the militarized squad of volunteers (part its members) from the rural district formed after the anti-Soviet Uprising in June 1941. At the end of July or beginning of August 1941 the first execution of Jews took place in the Kuprė forest , into which the adults were brought as if for work. Almost all Lithuanian guards did not know that Jews would be killed. The German police and two SD officers who finished off the wounded with the sub-machine gun series tried to achieve that each Lithuanian who was at the place of execution would shoot at least one Jew. Those who refused to shoot were threatened to be killed together with Jews, but instead some of them were just beaten. The massacre of the Jewish community of the Kražiai rural district illustrates the plan of Walter Stahlecker, Commander of the Operational Group A, for Germans to remain behind the scenes (in the second plan) and to create an image as if “the inhabitants liberated by Vermacht began themselves to apply the strictest measures against the Bolshevist and Jewish enemies”. At the end of August near Medžiokalnis (not far from the ghetto) another 70 Jews (mostly children) were shot, they were killed by the Lithuanian auxiliary police staff. About 20 Jews from the Kražiai rural district saved themselves; most were hidden by the local population.With the “critical mass” of local investigation about the death of the Jewish communities of townships and villages formed, it would be possible to supplement the historiography on the issues of the massacre of Jews in the province, to update some historiography approaches of Lithuanian and foreign historians about the holocaust in Lithuania, which was turned into the firing ground of the Jewish mass massacre by the German Nazis in 1941.
Keywords: Lithuania; German occupation; Holocaust; Kražiai